2017
DOI: 10.18203/2320-6012.ijrms20173009
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status vis-a-vis iodine deficiency in children of "Save Our Soul"children’s village in rural Varanasi: a micro-level study

Abstract: Background: There is paucity of data with regard to the Iodine deficiency in an organized sector like SOS children's village which is an independent, non-governmental, social development organization located in urban Varanasi. Uttar Pradesh is one of the endemic states for goiter. It is expected that similar situation of goiter may prevail in children as well. It is a matter of concern that micro nutrient deficiency and under-nutrition may exist side by side. The objectives of the study were to assess nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, this finding, being a cross-sectional study, does not necessarily infer the causal association between the use of iodized salt and malnutrition. Moreover, it suggested that adequately iodized salt fails to reach families who could potentially benefit the most [ 14 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding, being a cross-sectional study, does not necessarily infer the causal association between the use of iodized salt and malnutrition. Moreover, it suggested that adequately iodized salt fails to reach families who could potentially benefit the most [ 14 , 27 ].…”
Section: Discussionmentioning
confidence: 99%